2018
DOI: 10.4103/jispcd.jispcd_66_18
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of conventional rapid maxillary expansion versus alternate rapid maxillary expansion and constriction protocol combined with protraction headgear in the management of developing skeletal Class III malocclusion

Abstract: Aims and Objectives:The reverse pull headgear has been widely used to intercept a developing skeletal Class III malocclusion with maxillary deficiency. Rapid maxillary expansion (RME) is recommended along with the reverse pull headgear because there is disruption of the circummaxillary and intermaxillary sutures. This, in turn, expedites the orthopedic effect of the reverse pull headgear. However, studies have shown that the circummaxillary sutures may not be fully disrupted by the use of RME alone. The protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This might be related to the significant maxillary skeletal and dental changes seen in that group. Al-Mozany et al (36) , Parayaruthottam et al (47) , and Almuzian M. et al (31) also reported significant forward movement of the upper lip, only in the alternating rapid maxillary expansion and constriction group. Celebi and Celikdelen (32) , on the other hand, observed backward migration of the upper lip in both the RME and alternating rapid maxillary expansion and constriction protocols and explained this difference as a compensation between soft tissue and skeletal alterations.…”
Section: Discussionmentioning
confidence: 94%
“…This might be related to the significant maxillary skeletal and dental changes seen in that group. Al-Mozany et al (36) , Parayaruthottam et al (47) , and Almuzian M. et al (31) also reported significant forward movement of the upper lip, only in the alternating rapid maxillary expansion and constriction group. Celebi and Celikdelen (32) , on the other hand, observed backward migration of the upper lip in both the RME and alternating rapid maxillary expansion and constriction protocols and explained this difference as a compensation between soft tissue and skeletal alterations.…”
Section: Discussionmentioning
confidence: 94%
“…12,13 Studies in literature show that skeletal and soft tissue changes with Alt-RAMEC is better as compared to RME. [14][15][16][17] Both studies by Viera et al 18 and Dodelatour et al 19 reported more forward movement in the maxilla in the RME-treated group than most other studies. In 2010, Isci et al 20 compared the dentofacial effects of the 4week Alt-RAMEC protocol with the 1-week RME application in cases where maxillary protraction was needed.…”
Section: Discussionmentioning
confidence: 99%